(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The current research deals with formulation and evaluation of Benazepril hydrochloride transdermal films, by varying ratios of polymers Eudragit RL100, Eudragit RS100 by film casting technique. Preformulation studies were conducted to check the solubility, melting point and partition coefficient. The eleven formulations were analyzed for physicochemical parameters and drug dissolution potential of transdermal films. All the formulations are transparent with minimum weight variation and uniform thickness. The drug content uniformity of all the formulations vary between 96.84 ± 3.7% to 96.98 ± 1.6% indicate uniform drug distribution. The low water vapour transmission values indicate good water vapour permeation. The folding endurance is between 246 ± 4.60 to 315 ± 4.13 indicates that the transdermal films can withstand rupture. In vitro drug dissolution study indicates maximum amount of drug 96.8% (F2) released in 24 h when compared with marketed formulation 84.81%. The release order follows Fickian diffusion. The formulation F2 was optimized based on drug flux, permeability coefficient and enhancement ratio.